Pregnancy outcome in women who survived genital or extragenital cancer - Anis Cerovac; Dženita Ljuca; Gordana Bogdanović; Gordana Grgić; Haris Zukić (Medicinski glasnik, 2020)
Aim: To investigate clinical and obstetrical characteristics, an outcome and a prognosis for pregnant women with diagnosed and treated genital or extragenital cancer and their newborns. Methods: This retrospective cohort study included pregnant and childbearing women with a history of cancer diagnosed before pregnancy during the period between 1 January 2014 and 31 December 2018. Data related to the course of pregnancy and childbirth were collected from medical records (mothers' disease history and partogram). The analysis covered clinical and histopathological characteristics of cancers, type of the treatment (surgery, chemotherapy, radiotherapy), demographic data, obstetric characteristics, comorbidities of women, and outcome of the newborns. Results: The study recorded 18 414 deliveries, of which 30 (0.16%) were pregnancies in women who had been diagnosed and treated earlier for genital or extragenital cancer. The average age of the women at the time of delivery was 29.43±5.97 years. There were six (20%) women with genital and 24 (80%) with extragenital cancer. The most frequent extra genital cancer was Hodgkin lymphoma, in eight (26.6%) cases; ovarian cancer was the most frequent genital cancer, in four (13.3%) cases. The average time span from the cancer diagnosis and start of the treatment to the delivery was 59.2±44.4 months (5 years) (range 12 months-15 years). Two (6.6%) women died. Conclusion: Our data demonstrate a favourable obstetric and neonatal outcome for women who have survived cancer.
Keywords: fertility; malignancy; obstetric outcome; pregnancy